Photonic Integrated Circuits Challenges & Solutions: Homogenization, Polarization Management and Coupling - Samadian, Parya (Université d'Ottawa / University of Ottawa, 2015)
In recent years much effort has been carried out to make integrated photonics a widespread technology to be exploited in current optical communication industry. It is hoped by substituting microelectronics by photonic chips and keeping the light carried by optical fibers in light domain for further processing, the cost and speed of communications will be vastly improved. Although this transition is challenging in various aspects, here in this thesis some of these issues are discussed and addressed. In this thesis firstly the limitations of current simulation tools for analysis of wide range of photonic devices is pointed out. Structures based on photonic crystals are taken into consideration at this point which because of finely detailed structures have shown to be challenging to be analyzed by conventional tools. In this regard three different common structures based on photonic crystals in both resonant and non-resonant regimes have been considered: lamellar gratings, metamaterials for Lüneburg lens and Bragg gratings in a LC-DFB laser. For each structure, an analytical method or homogenization approach is proposed which is claimed to be faster for analysis of such components than numerical methods. Comparisons of the results with conventional numerical methods prove accuracies of each approach. Furthermore, fiber-to-chip coupling and polarization management are discussed as other important issues in the field of integrated photonics. Concerning polarization management, stepped waveguide approach will be introduced as the most promising approach for SOI and III-V substrates and designs based on this structure reported in literature are reproduced and inaccuracies are pointed out and corrected accordingly. Also regarding fiber-to-chip coupling, a critical appraisal of the most recent proposed structures for edge coupling will be offered and the results will be reproduced by simulation tools. At the end, based on detailed comparisons, the most encouraging approach with low insertion loss and easy fabrication steps is introduced and novel platform for easy butt coupling single mode fibers to the coupler structure is proposed.
Keywords: Photonic Integrated Circuits; Polarization Management; Coupling; Homogenization